Cost stickiness in the Italian Mutual Banks and comparison among Less Significant Banks - Piatti, Domenico; Cincinelli, Peter; Cattaneo, Cristiana; Bassani, Gaia (European Scientific Journal, ESJ, 2024)
This study investigates cost stickiness in the Italian banking system, with a specific focus on Less Significant (LS) banks, including Mutual Banks (MBs), during the period 2006-2019. The research seeks to identify whether LS banks exhibit asymmetric cost behavior, particularly in response to income and credit risk level variations. Utilizing a unique dataset of 5,446 observations and applying econometric models adapted from the seminal work of Anderson et al. (2003), this study provides a novel analysis of cost stickiness within a banking context, an area that has been underexplored in the existing literature. The results reveal significant cost stickiness across all LS banks, with MBs demonstrating more pronounced stickiness than other LS banks. Additionally, the findings show that higher levels of credit risk exacerbate cost stickiness, while greater efficiency mitigates this effect. These insights underscore the importance of tailored cost management strategies in the banking sector, particularly for MBs, and contribute to understanding the unique challenges LS banks face in Italy. The research’s originality lies in its focused examination of cost behavior within a distinct subset of the Italian banking system, providing new perspectives on how smaller, regionally-focused banks manage financial pressures.